2017
DOI: 10.1021/acs.jpcc.7b09499
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Molecular Films of Alkanethiols on Graphene for Heavy Metal Sensing

Abstract: We report a comparative study involving the formation of self-assembled molecular films by two types of alkanethiols (1-octadecanethiol and 1-dodecanethiol) on graphene grown via chemical vapor deposition, for heavy metal sensing applications. Scanning tunneling microscopy measurements confirm that the alkanethiol molecules can form localized, ordered molecular films on single-layer graphene despite the presence of structural and chemical irregularities. To test and compare the sensory characteristics associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…(Feng et al, 1997) The binding of Hg 2+ to the channel right-shifts the Dirac point, the effect of which is quite evident in the I DS -V GS curve of the device. A similar, comparative study conducted by Afsharimani et al shows that the same scheme, of functionalizing graphene with alkanethiols, is more sensitive to the presence of Pb 2+ ions (Dirac shift of 30.2 G 6.8 V) as compared to Hg 2+ (Dirac shift of 7.1 G 4.8 V) (Afsharimani et al, 2018). Both the studies exhibit detection of the analytes at 10 ppm concentration.…”
Section: Chemical Sensingsupporting
confidence: 58%
“…(Feng et al, 1997) The binding of Hg 2+ to the channel right-shifts the Dirac point, the effect of which is quite evident in the I DS -V GS curve of the device. A similar, comparative study conducted by Afsharimani et al shows that the same scheme, of functionalizing graphene with alkanethiols, is more sensitive to the presence of Pb 2+ ions (Dirac shift of 30.2 G 6.8 V) as compared to Hg 2+ (Dirac shift of 7.1 G 4.8 V) (Afsharimani et al, 2018). Both the studies exhibit detection of the analytes at 10 ppm concentration.…”
Section: Chemical Sensingsupporting
confidence: 58%
“…The high sensitivity to mercury was attributed to the presence of thiol groups in 1-octadecanethiol monolayer. Baykara and co-workers further demonstrated that chemically vapor grown graphene functionalized with 1-octadecanethiol could detect both mercury and lead ions at 10 ppm concentrations . The authors proposed that the electrostatic gating effect was responsible for the sensing behavior of the fabricated sensing devices.…”
Section: Sensing Applicationsmentioning
confidence: 99%
“…The outstanding sensitivity toward Hg 2+ was credited to occurrence of thiol group in ML 1‐octadecanethiol. Baykara and co‐workers [ 342 ] also confirmed that the CVD grown the 2D‐G functionalized with 1‐octadecanethiol can selectively analyze both Hg 2+ and Pb 2+ ions at 10 ppm concentrations. It is inferred that electrostatic gating consequence was accountable for sensing performance in manufactured sensor.…”
Section: Applications Of the Group IV 2d Xenesmentioning
confidence: 84%